#URL Holocaust digital Verhandlungen des Genozids zwischen Public History, Geschichtspolitik und Kommerz - Pfanzelter, Eva (innsbruck university press, 2023)
In 'Holocaust Digital,' the focus lies on the impact of digitalization on Holocaust discourses. It centers around the effects this has on collective memories and the perception of this historical event within German and English-speaking contexts. Due to the complexity of the subject, the study is methodologically interdisciplinary, exploring websites of selected memory institutions, networks, as well as selected social media, forums, and blogs. The results compellingly demonstrate that online media have led to multifaceted changes in the negotiations of the Holocaust. On the one hand, they significantly expanded access to information about the Holocaust, making it more multimedia-oriented and introducing a wider range of voices into the discussion. Thus, the online negotiation of the Holocaust has increasingly become interactive and participatory. On the other hand, these altered practices have also created space for misinformation, denial, and distortions. Furthermore, digitization has changed the way in which the memory of the Holocaust is shaped. Memorials, museums, and educational institutions increasingly use digital media to convey information. These changes not only shape how the Holocaust is perceived but also raise important questions about authenticity, culture of remembrance, and society's responsibility in the digital age.